Mapping the circulation of fat hatred. Issue 1 (2nd January 2020) - Rinaldi, Jen; Rice, Carla; Kotow, Crystal; Lind, Emma
ABSTRACT: The authors draw from affect theory and intersectionality-as-assemblage theory to conceptualize fatmisia as a complex affective force. In line with queer affect theorist Sara Ahmed's theorizing of emotion, the authors explore how fat hatred circulates as an affective economy: how it flows across, attaches to, and comes to define or value different bodies. The authors analyze interview data compiled for the research project Through Thick & Thin to map fat hatred circulating in healthcare contexts, on transit, and while exercising. The data yielded insight into how fat hatred obstructs access to public participation, resources, and services, by rendering public space and social exchanges uncomfortable, unwelcoming, unsafe, and inaccessible. Constellations of feelings that adhere to fat bodies become instruments of fatmisia, and operate relationally in the space between bodies with the object of erasing or expunging fat life.